Behavior of Nizhny Novgorod Diocese Clergy during First Russian Revolution - N. E. Archipova (Научный диалог, 2024)
This study examines the behavior of the clergy of the Nizhny Novgorod Diocese regarding the revolutionary events at the beginning of the 20th century. It identifies instances of oppositional behavior and its consequences for the priests of the Nizhny Novgorod Diocese during the period of 1905-1907. The novelty of the research lies in the fact that, for the first time in this article, based on materials from the Nizhny Novgorod Spiritual Consistory, attention is drawn to the anti-government sentiments and actions of representatives of parish clergy of the Nizhny Novgorod Diocese during the first revolution. It is shown that oppositional behavior was not widespread but rather isolated. The author concludes that it manifested as a protest against social injustice, military field courts, in defense of peasants’ rights to land against landlords, urging peasants to disobey authority, non-payment of taxes, church fees, association with politically unreliable individuals, liberal interpretation of the Manifesto of October 17, 1905, and so on. The author believes that the accused priests did not align themselves with a specific political party, except for Father I.I. Vladimirovsky, an archpriest from Arzamas and a deputy of the Second State Duma from the Constitutional Democrats party. It was found that 2 out of 4 cases against priests were dropped. Meanwhile, 3 out of 4 priests were punished by the diocesan authorities with a ban on serving or transfer to other parishes. The findings of this research can be utilized in courses studying the history of the Russian Orthodox Church.